Management Of Pediatric Pulmonary Tuberculosis Current Solutions And Challenges : Literature Review - jaya, Rikmal; saputra, silvino benny; lestari, nur asanti; junaiddin aana, muhamad; damayani, damayani; lestari, ira; anugrah, rifal; Purnamasari, Anisa (PT. Nursing Genius Care, 2025)
Background: Tuberculosis (TB) in children remains a significant global health concern, with many cases going undiagnosed. Mortality rates due to TB among children continue to rise, particularly in high-burden countries such as Ethiopia and South Africa. Purpose: This study aims to review various approaches and interventions that have been implemented to address the pediatric TB epidemic and assess their overall impact on child health. Methods: This study utilized Boolean terms, and a systematic literature search was conducted across several databases, including ScienceDirect, PubMed, and Google Scholar. Results: Diagnosis is often delayed due to non-specific symptoms and the difficulty of laboratory confirmation. While GeneXpert Ultra has improved detection accuracy, it has not fully addressed the diagnostic challenges. Conclusion: Findings indicate that screening and preventive treatment interventions are highly effective in improving child health outcomes. Although new diagnostic tools such as GeneXpert Ultra show great potential, significant challenges in the detection and management of pediatric TB remain. This review highlights the importance of a holistic approach to bridging the gaps in TB detection and treatment in children.